Dysbindin promotes pancreatic ductal adenocarcinoma metastasis by activating NF-κB/MDM2 via miR-342–3p. (1st May 2020) - Zhu, Donglie; Zheng, Shi; Fang, Cheng; Guo, Xin; Han, Dandan; Tang, Mingyao; Fu, Hang; Jiang, Mingzuo; Xie, Ning; Nie, Yongzhan; Yao, Xuebiao; Chen, Yong
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most invasive solid tumours and has the highest cancer-related mortality rate. Despite intense investigation, the molecular mechanisms underlying the invasiveness and aetiology of PDAC remain elusive. MicroRNAs (miRNAs) are key regulators of tumour cell plasticity, but their roles in PDAC metastasis have not been characterized. Our early studies showed that dysbindin protein levels are elevated in PDAC patients compared with control individuals and that dysbindin upregulation elicits PDAC cell proliferation via the PI3K pathway. Here, we show that dysbindin promoted PDAC metastasis via the NF-κB/MDM2 signalling axis. Increased dysbindin levels correlated with aggressive features in PDAC, and the overexpression of dysbindin significantly promoted PDAC metastasis and invasion in vitro and in vivo. Surprisingly, dysbindin was identified as a direct target of miR-342–3p, which promotes NF-κB activation and PDAC metastasis. Thus, dysbindin-mediated NF-κB activation via miR-342–3p represents a context-dependent switch that enables PDAC cell proliferation and metastasis. Our data suggest that dysbindin and miR-342–3p are potential leads for the development of targeted therapy for PDAC. Highlights: Dysbindin could promote PDAC metastasis and invasion in vitro and in vivo. Dysbindin could promote metastasis of PDAC via NF-κB/MDM2 signal axis. MDM2 is upregulated in PDAC tissues and correlated with clinicopathological characteristics of PDAC. Dysbindin is a direct target of miR-342–3p. Dysbindin overexpression could decrease the antitumour effect of miR-342–3p.